Methodology for requirements definition of complex space missions and systems. (September 2015) - Viscio, Maria Antonietta; Viola, Nicole; Fusaro, Roberta; Basso, Valter
Abstract: The paper deals with the description of a methodology to properly perform space mission design, with particular attention to derivation of requirements. Several tools are usually adopted to support the design of complex missions and systems, but no very rigorous processes are available for the derivation of requirements. The methodology proposed in this paper aims at providing a general approach to exploit the main system engineering analyses and tools for a thorough assessment of the requirements. Specifically, it addresses how each category of requirements can be derived by appropriate analyses and what is generally the sequence of derived requirements categories. The very first design step is mission statement and objectives definition. A parallel activity is the stakeholders׳ needs׳ analysis, mainly based on identifying all mission׳s actors and their expectations, thus deriving additional objectives. Once the broad objectives of the missions have been established, the following step of the design methodology is the Functional Analysis, which allows identifying the major functions to be performed for the mission׳s accomplishment, as well as the needed physical components. Another important analysis is related to the Concept of Operations, which has the scope of describing how the system is operated during its life-cycle phases to meet stakeholders׳ expectations. The overall process relies on the use of specific software tools, which provide useful means for the analyses integration giving also the chance to easily track and verify the results. The paper reports a detailed description of the methodology, as well as an example case study in order to provide a clearer understanding of the entire process. The analyzed case refers to in-orbit validation of inflatable technology, which is one of the most significant technologies to be developed for future human space missions to deep space targets. Future human exploration programs point towards new and more challenging objectives, which require the development of new advanced systems and technologies, and their demonstration in space environment. Indeed a system is considered flight-qualified, once it has completed a demonstration mission in space environment. Accordingly, there is a great interest in the definition and analysis of dedicated missions for the in-orbit demonstration of advanced technologies. The developed design methodology and the results obtained by applying the methodology have been obtained in the framework of STEPS-2 (Sistemi e Tecnologie per l'EsPlorazione Spaziale-Phase 2). STEPS-2 is a research project co-founded by EU on the "Misura Piattaforme Innovative"-Phase 2 of POR FESR 2007/2013. Highlights: A methodology to support complex space missions and systems design is presented. The methodology allows a sequential and rational derivation of requirements. Derivation of different categories requirements from appropriate analyses is discussed. Inflatable technology in orbit demonstration mission is discussed as case study.